Plant design for the extraction and manufacture of papaverine cinchonidine and rutin tablets from lagundi leaves - Eusebio, Manuel; Franco, Chito; Gervacio, Lily.; Natividad, Ronaldo (Diliman, Quezon City College of Engineering, 1986)
A design proposal for the construction of an industrial plant will extract and purify three pharmaceutical products from the active principles of lagundi, a local herb. Raw material: Lagundi (Vitex Negundo, L.) -- Products: Papaverine HCl (analgesic), Cinchonidine (expectorant), Rutin (cardiovascular) -- Process description: Extraction of the active principles through selective solvation based on the different solubility characteristics of these principles and the undesired mass. In between each extraction process are intermediate steps for the recycling of the solvents and further purification of the end products. The isolated and purified principles are then tabletted and packaged for distribution and marketing. -- Plant site: Calamba, Laguna -- Area requirements: Agricultural 50 hectares, Manufacturing 0.1 hectares -- Plant capacity: Papaverine HcL 5,215,200 tab/yr, Cinchonidine 3,160,800 tab/yr, Rutin 6,343,200 tab/yr -- Total production: 14,719,200 tab/yr, maximum total production was based on a target of 3.8% of the market share -- Fixed capital investment: P 56.1 M -- Working capital: P 5.6M -- Total capital investment: P 61.7 M -- Product cost: P 6.6M -- At 70% capacity Net profit: P 8.4M -- % Profit on sales (after taxes): 36.8% -- % return on investment (after taxes): 13.6% -- Pay out period: 4.6 years -- Break even point: 8.75% maximum capacity
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Drug factories; Pharmaceutical industry